The acceptability of vaginal smear self-collection for screening for cervical cancer: a systematic review - Natalia Serrano Doratioto Faria Braz; Noely Paula Cristina Lorenzi; Isabel Cristina Esposito Sorpreso; Lana Maria de Aguiar; Edmund Chada Baracat; José Maria Soares-Júnior (Clinics)
Cervical cancer is a major cause of death in adult women. However, many women do not undergo cervical cancer screening for the following reasons: fear, shame, physical limitations, cultural or religious considerations and lack of access to health care services. Self-collected vaginal smears maybe an alternative means of including more women in cervical cancer screening programs. The objective of this systematic review was to evaluate the acceptability of vaginal smear self-collection for cervical cancer screening. We selected articles from PubMed, the Cochrane Library and Embase that were published between January 1995 and April 2016. Studies written in English, French, Italian, Portuguese or Spanish that involved women between 18 and 69 years of age who had engaged in sexual intercourse were included in this review. The review was performed in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement. Nineteen studies were ultimately evaluated in this review. Most of the included studies (n=17) demonstrated that the self-collection method exhibited outstanding acceptability among women with respect to cervical cancer screening, and only two studies indicated that self-collection exhibited low acceptability among women in this context. The acceptability of self-collection was determined subjectively (without standardized questionnaires) in 10 studies (53%) and via structured and validated questionnaires in the remaining studies. The results of our review suggest that the self-collection method is well-accepted and may therefore encourage greater participation in cervical cancer screening programs. However, additional studies are required to verify these results.